Inês de Castro no romance contemporâneo português - Souza, Aldinida de Medeiros (2010)
Ines de Castro is a theme in literature from the fourteenth century. The historical fact of his death, in 1355, became a landmark in the history of Portugal and, since then, several literary texts from various genres, have dealt with this theme, this made the couple Pedro and Ines a myth of love passion, of love beyond the barriers of death, like Tristan and Isolde, Romeo and Juliet, Abelard and Heloise. The literary myth - or any picture that mythologize literature - is always prepared before culturally and works in the same way that so many others, this is, as an element of cultural identity, either collectively or individually, making it also a feature poetic. Thereby, is an archetype confirmed through time and eventually reveals a series of webs of the human psyche. Ines de Castro became the Portuguese myth of eternal love: she became queen after your dead. The persistence of the myth makes the love story of Pedro and Ines continue to produce texts of various literary genres. This study examines six contemporary historical novels, to show that the way actually this kind o novel does a new formulacion of Pedro e Ines mythical, because now it s different view likes the victim in Os lusiadas and other texts from the past. Collaborate to this news relacions between history and literature and a novelist's new stance in relation to historical facts that relate like reffering to novel. The intention is to show, through the novels chosen now Ines de Castro have different profiles than it had before in tradicional historic novels from the period of Romanticism and New Romanticism. Authored by Agustina Bessa-Luís, João Aguiar, António Cândido Franco, Seomara da Veiga Ferreira and Luis Rosa, the six novels studied show the circularity cultural of inesian myth showing this new character of the new person Ines in the contemporany historical novel